Investigating the Performance of TIN-Based Perovskite Solar Cell with Zinc Selenide as an ETM and Graphene as an HTM Using SCAPS-1D - Ijeoma Ukorah; Adeyemi Owolabi; Haruna Ali; Muhammed Onimisi; RA Tafida; Awujoola J Olalekan; Hassan Muhammed Gambo; Sakinate L Usman; Akusu Christiana; Jessica M Ukwenya; Bankole J Akinade; RU Ugbe (Progress in Physics of Applied Materials)
In this study, a numerical analysis was conducted on a Sn-based planner heterojunction perovskite device. Structure of Glass/TCO/ETL/CH3NH3SnI3/HTL/Metal was performed by using the solar cell device simulator SCAPS 1D. The absorber layer is a tin-based methylammonium tin iodide (CH3NH3SnI3), while the electron transport layer (ETL), ZnSe, and a hole transport layer (HTL) Graphene, were used. To optimize the device, the thickness of the ETL, absorber, and HTL doping concentrations were varied, and their impact on device performance was evaluated. The effect of temperature variations was also investigated. The optimum absorber layer thickness was found at 950 nm for the proposed structure.  The acceptor concentration improved the device performance significantly. The optimized solar cell achieved a PCE, Voc, Jsc, and FF of 25.40%, 0.959 V, 32.863 mA/cm2, and 80.60%, respectively. The proposed cell structure also possesses excellent performance under high operating temperatures indicating great promise for eco-friendly, low-cost solar energy harvesting.